The predictive power of biomarker macrophage migration inhibitory factor in patients with st- segment elevation myocardial infarction. (14th October 2021) - Vishnevskaya, I; Kopytsya, M P; Storozhenko, T Y E
Abstract: : Biomarkers have been taken one of the first places as diagnostic and prognostic tools in acute myocardial infarction (AMI). They are used both in the acute and in the long-term periods of the disease to predict various adverse events Their especially important property is the ability to predict the long-term adverse events of the disease, which can significantly improve the outcome. One of the promising biomarkers for the early adverse outcome prediction is the proinflammatory cytokine macrophage migration inhibitory factor (MIF). Purpose: To determine the MIF significance in 1-year adverse outcomes prognosis after AMI. Methods: 130 ST-segment elevation myocardial infarction (STEMI) patients (72.6% male and 27.4% female) were enrolled, mean age was 58.25±1.22 years. Control group of 12 healthy volunteers included. All patients underwent a baseline investigation which includes standard electrocardiography, echocardiography with strain, angiography, and determination of marker of myocardial necrosis – cardiac troponin T. Also, the level of MIF, soluble suppression of tumorigenicity-2 (sST2), C-reactive protein determined during the first 12 hours after the STEMI, before the percutaneous coronary intervention (PCI), 6 hours, and 24 hours after the PCI. The endpoint was composite and included all-cause mortality, nonfatal myocardial infarction, nonfatal stroke, and hospitalization for unstable angina, acute decompensated heart failure. During 1-year follow-up 18% of patients reached the endpoint. Results: The effect of several variables of clinical, instrumental and laboratory status were assessed on reaching the endpoint by patients. We have found that MIF level determined before PCI (AUC 0.73; p=0.003; 95% Cl: 0.613 – 0.826) might be a significant independent predictor of mortality with sensitivity (Se) 70% and specificity (Sp) 80%. MIF level 6 hours after PCI showed even better result (AUC 0.8; p=0.002; 95% Cl: 0.64 – 0.9; Se 74%, Sp 82%). MIF >3934 pg/ml associated with the highest risk of adverse events. For identification of the main risk factors for adverse outcome, we have used logistic regression method. The MIF level determined before the PCI was the most important to predict adverse outcomes (odds ratios is 1.0006, p=0, 0038; x2=4.58). Areas under the ROC for the model was equal to 0.8; 95% Cl: 0.58 to 0.89). Neither sST2 nor CRP have not shown any significant results (p<0.05). According to the data of the Kaplan-Meier survival analysis, long-term survival after STEMI was significantly lower in patient with the level of MIF determined during the first 12 hours after the event more than 2988 pg/ml (Log-rank = −4, 891, p=0.014). Conclusions: Biomarker MIF has showed as an independent tool associated with the risk of adverse outcome 1 year after STEMI. MIF could be used in routine clinical practice to improve risk stratification of patients with STEMI. FUNDunding Acknowledgement: Type of funding sources: None.